Oxyporus-Studien-II. Oxyporus (Oxyporus) procerus Kraatz und O. (Oxyporus) ruzickai spec. nov. aus China (Coleoptera, Staphylinidae, Oxyporinae) | Oxyporus procerus Kraatz und O. ruzickai spec. nov. - Schülke, Michael (Contributions to Entomology = Beiträge zur Entomologie, 2017)
Types and additional material of Oxyporus (Oxyporus) procerus Kraatz, 1879 are revised. Oxyporus chenpengi Li, 1992 is synonymised with O. procerus. Oxyporus (Oxyporus) ruzickai spec. nov. from the Chinese provinces Gansu and Yunnan is described. Both species are illustrated and their distributions are mapped. Nomenclatural Acts Oxyporus (Oxyporus) ruzickai spec. nov. - urn:lsid:zoobank.org:act:BD64C07C-1AEC-4800-9EC8-A7EFA28367CB